(untitled) (Quaderni di Gargnano, 2018)
After an introductory overview of the textual tradition of Angelo Poliziano’s vernacular letters (40 of which are available to us today), the essay focuses on some ecdotic and exegetical questions that captured the attention of the author as she was working on the critical edition of the Letters. Without pretending to offer a systematic approach to the subject, the article offers several practical examples of the sort of documentary and historical analysis that went into producing the commentary to the Letters.